Autophagy and the pancreas: Healthy and disease states - Zhou, Zixian; Zhang, Pengcheng; Li, Juan; Yao, Jiaqi; Jiang, Yuhong; Wan, Meihua; Tang, Wenfu; Liu, Ling (Frontiers in Cell and Developmental Biology, 2024)
Macroauto phag y/autophagy is an intracellular degradation pathway that has an important effect on both healthy and diseased pancreases. It protects the structure and function of the pancreas by maintaining organelle homeostasis and removing damaged organelles. A variety of pancreas-related diseases, such as diabetes, pancreatitis, and pancreatic cancer, are closely associated with autophagy. Genetic studies that address autophagy confirm this view. Loss of autophagy homeostasis (lack or overactivation) can lead to a series of adverse reactions, such as oxidative accumulation, increased inflammation, and cell death. There is growing evidence that stimulating or inhibiting autophagy is a potential therapeutic strategy for various pancreatic diseases. In this review, we discuss the multiple roles of autophagy in physiological and pathological conditions of the pancreas, including its role as a protective or pathogenic factor.